Aumento do aporte de pólen em colônias de abelhas Apis mellifera pela indução do florescimento da jurema preta (Mimosa tenuiflora) durante o período seco na caatinga do baixo jaguaribe cearense - Silva, Aline dos Santos (2013)
This study aimed to investigate the possibility of inducing blooming by Mimosa tenuiflora, a plant species of common occurrence and abundance in Caatinga (shrub vegetation of NE Brazil), in order to provide pollen for honey bees (Apis mellifera) in the dry season, as well as to evaluate the use or not of this resource by bees, besides studying the floral biology of this plant species and its flower visitors. The experiment was carried out at Apiário Altamira Apícola in the county of Limoeiro do Norte, state of Ceará, Brazil, from August to December 2012. Fifteen plants were chosen and split into five groups of treatments to receive different levels of water (T1 = 0 L, T2 = 250 L, T3 = 500 L, T4 = 750L and T5 = 1,000 L) to investigate the beginning, peak and decline of the blooming stages. In order to collect pollen samples, ten apiaries were selected, each one with twelve colonies of Africanized honey bees. The apiaries were split in two treatments in a way that the five apiaries of Treatment 1 were at distances greater than 3 km to the sites where M. tenuiflora plants were induced to bloom, while apiaries of Treatment 2 were only 20 m away of the blooming plants. Three colonies out of the twelve present in each apiary were randomly chosen to receive pollen collectors, totalizing fifteen colonies with collector per treatment. Pollen samples were collected at 7:30h and 17:30h, three days before the blooming of M. tenuiflora and then three days during the flowering period. The results showed that on the first day of blooming – which is equivalent to the eighth day after flowering induction –, only plants submitted to treatments 3, 4 and 5 presented blooming, and the largest number of inflorescences was obtained in T5 – 1.000 L, which differed significantly (p<0.05) to the other treatments. Apis mellifera began to collect resources at 5:00h and stopped at 7:00h, collecting only pollen. The other flower visitors were Trigona spinipes, Melipona subnitida and some wasps, but in a lower frequency of visitation. Pollen analysis showed that M. tenuiflora contributed 59.16% in the pollen diet of bees from colonies of Treatment 2 and only 9.81% in the colonies of Treatment 1. Thus, we concluded that M. tenuiflora is a species that, once in bloom, increases the offer and collection of pollen by bees during the dearth period of the year, exempting the use of alternative protein feeds. Therefore, it is of paramount importance to conserve and increase the number of M. tenuiflora plants in places where beekeeping is practiced.